Transformasi Digital dalam Meningkatkan Keunggulan Kompetitif: Studi pada UKM di Bandar Lampung - Arifa Kurniawan; Andika Saputra (MANABIS: Jurnal Manajemen dan Bisnis, 2024)
Digital transformation has become a crucial factor in improving the competitiveness of small and medium-sized enterprises (SMEs) in the modern era. By utilizing digital technology, SMEs can accelerate operations, expand market reach, and build closer customer relationships. This research aims to explore how digital transformation contributes to the competitive advantage of SMEs in Bandar Lampung, while identifying the challenges faced in its implementation. The research used a descriptive qualitative approach, with data collected through in-depth interviews, observation, and document analysis of 10 SMEs that have adopted digital technology. The results show that digital transformation improves operational efficiency through process automation and better data management. In addition, digital technology expands market access through e-commerce platforms and social media, allowing SMEs to reach customers beyond the local area. Customer relationships are also becoming stronger through responsive communication and technology-driven interactions. However, the study found that the main challenges faced are limited digital literacy among SMEs and the high cost of technology implementation. Thus, support from the government and relevant institutions is needed to facilitate the adoption of digital transformation, particularly through training and technology subsidies.